Sibling Facilitation Mediates the Association Between Older and Younger Sibling Alcohol Use in Late Adolescence. (14th July 2014) - Samek, Diana R.; McGue, Matt; Keyes, Margaret; Iacono, William G.
Abstract : Previous research has shown adolescent siblings are similar in their alcohol use and that this similarity is largely due to their shared environment. Using a genetically informed sibling sample (196 full‐biological pairs, 384 genetically unrelated pairs), we confirmed that the extent to which older siblings facilitate younger siblings' alcohol use (i.e., help them get alcohol) was one factor contributing to this shared environmental association. All analyses controlled for parent and peer influences. Findings were not moderated by sibling differences in genetic relatedness, gender, or ethnicity. Proximity in sibling age strengthened these associations, somewhat. Results were especially strong for sibling pairs where the older sibling was of legal drinking age. Implications for prevention and intervention are discussed.